The consequences of short-term grazing of bioactive forages on established adult and incoming larvae populations of Teladorsagia circumcincta in lambs - Tzamaloukas, Ouranios; Athanasiadou, Spiridoula; Kyriazakis, Ilias (My University, 2005)
The objective of this study was to investigate the consequences of short-term grazing on bioactive forages on (i) the viability and fecundity of established adult Teladorsagia circumcincta population and (ii) the establishment and development of incoming T. circumcincta infective larvae. Forty-eight, parasite naive, 3-month old, grazing lambs were artificially infected with 8000 infective larvae of T. circumcincta on day 1 of the experiment. On day 21 p.i., lambs were allocated to one of three bioactive forage grazing treatments; chicory (Cichorium intybus), sulla (Hedysarum coronarium), lotus (Lotus pedunculatus), and the control grass/clover (Lolium perenne/Trifolium repens) forage. On day 28 of the experiment a second dose of 8000 T. circumcincta infective larvae was administered to the lambs to investigate the effects of forages on the ability of infective larvae to establish within the host. All animals were slaughtered for worm recovery on day 35, while liveweight gain, feacal egg counts (FEC) and total worm egg output were monitored regularly throughout the experiment. Although FEC or total egg output were similar among the groups, adult worm burdens at slaughter were significantly affected (P<0.05) by forage treatment during the 2 week grazing period. Lambs grazing chicory had the lowest adult worm burdens and significantly lower numbers of male worms compared to those grazing on grass/clover (P<0.01), while the lambs grazing on sulla or lotus had similar adult populations to grass/clover fed animals. The results from the worm recoveries of the second dose (immature worm burdens) were affected by physiologically and/or immunologically mediated mechanisms, which reduced larval establishment in all treatments. Nevertheless, immature worm burdens at slaughter were similar between chicory, sulla and grass/clover group, while the immature worm recoveries from the lotus group were significantly higher (P<0.05) compared to those from lambs grazing grass/clover. Overall, the results of the present study support the view that chicory can be a promising candidate species in pasture management practices to control T. circumcincta burdens
Keywords: Chicory; Nematoda; Sheep; Forage; Grazing; Euthanasia of animals; Animal experimentation; Immunology; Lambs; Parasites